Extreme Peripheral Blood Plasmacytosis Mimicking Plasma Cell Leukemia as a Presenting Feature of Angioimmunoblastic T-Cell Lymphoma (AITL) - Sokol, Kelsey; Kartan, Saritha; Johnson, William T.; Alpdogan, Onder; Nikbakht, Neda; Haverkos, Bradley M.; Gong, Jerald; Porcu, Pierluigi (Frontiers in Oncology, 2019)
Angioimmunoblastic T-cell lymphoma (AITL) is one of four major subtypes of nodal peripheral T cell lymphoma, characterized by its cell of origin, the follicular helper T-cell (TFH). Patients typically present with prominent constitutional (B) symptoms, generalized lymphadenopathy, hepatosplenomegaly, cytopenias, and rash. Here we present a case of a 62-year-old male with progressive cervical adenopathy, fevers and weight loss presenting with extreme polyclonal plasmacytosis and high plasma EBV viral load. While the initial presentation appeared to mimic plasma cell leukemia or severe infection, lymph node biopsy and bone marrow biopsy confirmed a diagnosis of AITL. This case highlights the heterogeneity of the clinical presentation of AITL to enable physicians to more promptly recognize, diagnose and initiate treatment.